Hydrology and pollution assessment in a coastal estuarine system. The case of the Strymonikos Gulf (North Aegean Sea) - PAVLIDOU, A.; HATZIANESTIS, I.; SKLIVAGOU, E.; PAPADOPOULOS, V.; ZERVAKIS, V. (Mediterranean Marine Science, 2002)
Three hydrographic cruises were undertaken to study the hydrology and to estimate the ecological status of the coastal ecosystem of the Strymonikos Gulf (North Aegean Sea) impacted by the riverine waters of the Strymon River. Surface sediments were also collected in order to determine the levels of organic contaminants in the gulf. Three main water masses were identified in the Strymonikos Gulf throughout the year: a) the surface river plume water, b) the surface and subsurface Black Sea Water and c) the near bottom (>50 m) water of Levantine origin. High nutrient concentrations were recorded close to the mouth of the river, indicating a rather eutrophic environment, which was restricted near the river discharge. The salinity-nutrient correlations of the surface waters of the study area were linear, indicating that the riverine waters are the major source of nutrient in the gulf. DIN:P ratios varied seasonally from relatively higher values during winter and early spring to lower values in late spring-early summer. This led to a shift from likelihood P-limitation during winter and early spring to N-limitation in late spring – early summer. Total hydrocarbon concentrations measured in the sediments ranged from 19.2 to 95.9 μ g/g, whereas total polycyclic aromatic hydrocarbon (PAH) values varied between 107.2 and 1019 ng/g. The application of different diagnostic criteria suggests a natural terrestrial origin for aliphatic hydrocarbons and pyrolytic origin for the PAHs. DDTs displayed the highest concentrations of all the organochlorines determined, whereas polychlorinated biphenyl (PCBs) concentrations were very low. Riverine input seems to be the major source for all the compounds identified.